Influence of Management of Entrepreneurship Education Programme on Job Creation Skills of Undergraduates in State Universities in North East Nigeria (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This study determined the influence of management of entrepreneurship education programme on job creation skills of undergraduates in public universities in North-East, Nigeria. Three research questions were raised and answered while three corresponding null hypotheses were formulated and tested by the study. The study employed an expo facto research design. The population for the study was with 2,405 students from six state universities in the North-East Nigeria. The sample of 331 respondents were determined Krejcie and Morgan (1970) sample size Table and were selected using a multistage sampling technique. A-15 items structured questionnaire titled: Management of Entrepreneurship Education and Job Creation Questionnaire (experts), was developed by the researchers from literature reviewed and used for data collection. The MEEJCAQ was validated by three Entrepreneurship Education and Measurement experts in Taraba State University. The validated MEEJCAQ was subjected to reliability analysis using Undergraduate students in North Central Nigeria and Cronbach Alpha coefficient of 0.89 was obtained. The MEEJCAQ was administered by the researcher with the help of three research assistants and data collected were analyzed using Mean and standard deviation to answer the research questions while chi-square test of goodness -of- fit was used to test the null hypotheses at 0.05 level of significance. The results obtained showed planning for Entrepreneurship Education programmes has significant influence on jobs creation of undergraduates in state universities in North-East Nigeria, there are five ways in which coordinating resources for Entrepreneurship Education programmes influences students' propensity to create jobs in state universities in North-East Nigeria and there are five ways in which organizing Entrepreneurship Education programmes influences students' ability to create jobs in state universities in North-East Nigeria. The study recommends that university administrators should effectively plan Entrepreneurship Education programmes in order to facilitate smooth teaching and learning in schools, coordinating resources for Entrepreneurship Education programmes must be adequate done by administrators and stake holders to ensure a fair students-resource ratio which is critical to achievement of the objectives of entrepreneurship Education and Entrepreneurship Education programme activities should be properly and regularly organized for continuous acquisition and development of job creation skills by undergraduates.